80 fs passively mode-locked Er-doped fiber laser. (1st May 2015) - Boguslawski, Jakub; Sotor, Jaroslaw; Sobon, Grzegorz; Abramski, Krzysztof M
Abstract: In this paper, 80 fs pulse generation from an all-fiber Er-doped laser is reported. The laser is mode-locked by a nonlinear polarization evolution mechanism in a stretched-pulse regime. Ultrashort pulses are generated directly from a ring-shaped, dispersion-managed cavity with a repetition rate of 31.9 MHz and 0.47 nJ of pulse energy. The laser has an all-fiber design, including the dispersion compensation and external compression stages, forming a robust and compact device.